Optimization of a CMOS-MEMS Resonator for Applications of Relative Humidity Measurement - FADLALLA, MOHAMED AHMED ELTAYEB (Universiti Teknologi PETRONAS, 2017)
The mathematical modeling and the finite element analysis (FEA) of a Complementary Metal Oxide Semiconductor-Microelectromechanical System (CMOS-MEMS) resonator has been presented. The resonator is designed based on 0.35 µm CMOS foundry fabrication technology. The sensing principle of the resonator is based on the change in resonance frequency of the CMOS-MEMS resonator due to adsorption/absorption or desorption of humidity on the active material layer of deposited on the moving plate that results in changes in the mass of the device. Simple analytical models of the CMOSMEMS resonator are generated to achieve estimates of the device performs. The effect of changes in lengths and widths of the beams on spring constant, resonance frequency, damping coefficient and quality factor (Q) are investigated. The spring constant is found to decrease with increase the lengths of the beam and increasing with increase the widths of the beam.